2018
DOI: 10.1021/acschembio.8b00466
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Inhibition of α-Synuclein Aggregation and Toxicity in Vitro and in Vivo by Trodusquemine

Abstract: The aggregation of α-synuclein, an intrinsically disordered protein that is highly abundant in neurons, is closely associated with the onset and progression of Parkinson's disease. We have shown previously that the aminosterol squalamine can inhibit the lipid induced initiation process in the aggregation of α-synuclein, and we report here that the related compound trodusquemine is capable of inhibiting not only this process but also the fibril-dependent secondary pathways in the aggregation reaction. We furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
160
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(179 citation statements)
references
References 67 publications
16
160
3
Order By: Relevance
“…Such compounds have the potential to serve in a therapeutic capacity by targeting specifically the microscopic steps of Aβ 42 that are responsible for oligomer production and proliferation [15][16][17][18][19] . Similar strategies have been employed to identify species that inhibit oligomer formation by αS, in particular by targeting the microscopic step of fibril amplification [20][21][22] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such compounds have the potential to serve in a therapeutic capacity by targeting specifically the microscopic steps of Aβ 42 that are responsible for oligomer production and proliferation [15][16][17][18][19] . Similar strategies have been employed to identify species that inhibit oligomer formation by αS, in particular by targeting the microscopic step of fibril amplification [20][21][22] .…”
mentioning
confidence: 99%
“…Despite the distinct mechanisms of the aggregation of αS and Aβ 42 and the differing effects of trodusquemine on the underlying processes, however, these effects resulted in a lower steady-state concentration of oligomers in both cases, in spite of the accelerated overall aggregation process in the case of Aβ 42 28 . Moreover, this molecule was found to suppress the toxic effects of both αS and Aβ 42 oligomers in cultured human neuroblastoma cells by markedly reducing the affinity of these aggregates for the cell membrane 20,28 . We also found that squalamine, an aminosterol comparable in structure to trodusquemine but with one less positive charge in its polyamine chain, similarly reduces the toxicity of αS oligomers to cells by their displacement from cell membranes 22 .…”
mentioning
confidence: 99%
“…74 However, the concentration of Ca 2+ required to induce a-synuclein aggregation in free solution is far higher than that required in order to induce aggregation at a hydrophobic glass surface. 74 For a binding site of Ca 2+ , study shows that Ca 2+ binds to the C-terminal domain (126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140) however, currently there is no information which particular residue is involved in the binding process. 74 There is currently a lack of information about the effect of Pb on aggregation in vitro, although it has been demonstrated that Zn 2+ , Al 3+ and Pb 2+ enable methionineoxidized a-synuclein, 75 to form aggregates at the same rate as the non-oxidized a-synuclein.…”
Section: A-synucleinmentioning
confidence: 99%
“…Understanding how protein aggregation works has led some scientists to develop anti-aggregation drugs against TP and a-synuclein. [134][135][136] More systematic experiments designed to clarify this relationship are vital, as they may provide the groundwork to produce better therapeutics. Therefore, further research with more rigorous and detailed studies are necessary to denitively uncover the relationship between metal ions and their effects on the aggregation of proteins, with a particular emphasis on their concentrations and relative ratios.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Recently, a squalamine derivative, called trodusquemine, has been shown to affect the aggregation of α-syn as well [ 36 ]. In addition to displacing α-syn monomers similar to the mechanism fulfilled by squalamine, trodusquemine directly interacts with α-syn to inhibit the secondary nucleation of aggregation [ 36 ].…”
Section: The Main Classes Of Anti-amyloid Compoundsmentioning
confidence: 99%